Detection of metallo-beta-lactamase-producing genes blaSPM and blaNDM in Pseudomonas aeruginosa isolated from wastewater in Southern Brazil - Vinícius Monteagudo de Barros; Bruna Seixas da Rocha; Jaqueline Rhoden; Janaína Franciele Stein; Simone Ulrich Picoli; Caroline Rigotto (IWA Publishing, 2024)
Pseudomonas aeruginosa is commonly associated with the ability to acquire antimicrobial resistance. The surveillance of resistance genes in various environmental matrices has gained prominence in recent years, being seen as a potential threat to public health. The objective of this study was to investigate genes encoding metallo-beta-lactamases (MBLs), which confer resistance to carbapenems, in wastewater. Fifteen isolates of P. aeruginosa were collected for five months from samples obtained from a municipal wastewater treatment plant in Rio Grande do Sul. These isolates were subjected to disk diffusion testing using 10 different antimicrobials. Phenotypic enzymatic tests for MBLs were conducted, and positive isolates underwent DNA extraction and gene detection using the polymerase chain reaction. The resistance rate to ceftazidime was 100%, cefepime 73.3%, piperacillin-tazobactam 66.67%, imipenem 53.30%, levofloxacin 46.67%, tobramycin 40%, and ciprofloxacin and amikacin 13.33%. Both meropenem and aztreonam resistances were rare accounting for 6.60% of the tested isolates. Among these isolates, 20% were classified as multidrug-resistant and were found to carry the blaNDM and blaSPM genes. The results suggest that evaluating resistance genes in bacteria from urban raw sewage can provide data that assist in surveillance, as this environment can stimulate increased bacterial resistance. HIGHLIGHTS Twenty per cent of P. aeruginosa isolates were classified as multidrug-resistant (MDR).; Urban sewage, which is associated with hospital sewage contributes to the spread of antimicrobial resistance genes (ARGs).; Three isolates carrying genes encoding MBLs presented resistance to beta-lactam antibiotics.; P. aeruginosa showed resistance characteristics to different classes of antibiotics and may have suffered stress of anthropogenic origin.;